2005
DOI: 10.1007/bf03027453
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of equal channel angular pressing and cold rolling in the evolution of microstructure and texture in zirconium

Abstract: Evolution characteristics of the microstructure and texture of severely deformed commercial purity Zr702 were studied. The mode of the severe deformation was either heavy cold rolling or equal channel angular (ECA) pressing. Equiaxed grains, present prior to the deformation, became elongated during deformation along the rolling direction or along the maximum shear direction for the case of cold rolling or that of ECA pressing, respectively. ECA pressing transformed the initial fiber texture to a quite differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[6,7] In this regard, previous investigations have shown that microstructure evolution is dominated by an increase in the fraction of high-angle grain boundaries (HAGBs) rather than grain refinement per se as the strain is increased above a value of ϳ3, i.e., the grain size is not decreased further at high strains. [4,36,37] Such an increase in HAGBs during SPD may lead to an increase in the GBS rate, resulting in higher values of m and, hence, higher total elongations. Nonetheless, the scaleup potential of ECAP is certainly greater than that of HPT, provided the production challenges associated with the requirement for low-strain-rate isothermal ECAP of Ti-6Al-4V can be met.…”
Section: B Total Elongationmentioning
confidence: 99%
“…[6,7] In this regard, previous investigations have shown that microstructure evolution is dominated by an increase in the fraction of high-angle grain boundaries (HAGBs) rather than grain refinement per se as the strain is increased above a value of ϳ3, i.e., the grain size is not decreased further at high strains. [4,36,37] Such an increase in HAGBs during SPD may lead to an increase in the GBS rate, resulting in higher values of m and, hence, higher total elongations. Nonetheless, the scaleup potential of ECAP is certainly greater than that of HPT, provided the production challenges associated with the requirement for low-strain-rate isothermal ECAP of Ti-6Al-4V can be met.…”
Section: B Total Elongationmentioning
confidence: 99%
“…After the cold rolling process, the influence of slip did not alter the bimodal distribution of the texture; it merely transformed the < 11 -20 >//RD texture into the < 10 -10 >//RD texture. Zirconium alloy, with its a typical close-packed hexagonal structure and its texture after cold rolling deformation is not only affected by the availability of slip, but also by the twin deformation mechanism, which plays an important role [33].…”
Section: Twinning Characteristics During Cold Rollingmentioning
confidence: 99%
“…[1] Especially during hot rolling of stainless steels, the sticking usually appears at rear parts of roughening rolls or at front parts of finishing rolls, and leaves various defects such as dents or scratches on surfaces. [2][3][4][5][6] This also induces problems of reduction in roll life and hot-rolling productivity, and seriously deteriorates the surface quality of rolled products. At hot-rolling plants, instead of coming up with fundamental solutions to this sticking problem, it is generally addressed by making adjustments in hotrolling conditions according to rolling plans, for instance, by controlling the kind of lubricants or the spraying amount used to reduce the friction coefficient between rolls and rolled plates.…”
Section: Introductionmentioning
confidence: 99%